Eukaryotic Voltage-Gated Sodium Channels: On Their Origins, Asymmetries, Losses, Diversification and Adaptations - Fux, Julia E.; Mehta, Amrit; Moffat, Jack; Spafford, J. David (Frontiers in Physiology, 2018)
Appearance of highly sodium selective voltage-gated sodium channels with rapid gating kinetics was a limiting factor in the evolution of nervous systems. Two rounds of domain duplications in a basal eukaryote generated a common ion channel template that is shared amongst voltage-gated sodium (Nav1, Nav2) and calcium channels (Cav1, Cav2, Cav3). Conservation of intron splice junctions in the first domain, including a rare U12-type from the minor spliceosome provides support for a shared, distant heritage of sodium and calcium channels. The consequences of a 4x6 transmembrane domain configuration is the emergence of a uniquely asymmetrical domains with a shared architecture. This configuration permits a highly changeable ion selectivity from calcium to sodium ion selectivity by means of a single lysine residue change in the high field strength site of the ion selectivity filter. A non-selective, and slowly-gating Nav2 channel appearing in single cell eukaryotes before the split of animals and fungi, evolved into ten Nav1.x channel genes specialized for vertebrate tissues. A close kinship is evident in the sharing of most intron splice junctions between Nav2 and Nav1 channels. Multicellularity and the appearance of nervous systems was an impetus for Nav1 channels to adapt to high sodium ion selectivity and fast ion gating. Specific nervous system adaptations include a capacity for modulation by protein kinase phosphorylation and tethering elements to protein assemblies in First Initial Segments and nodes of Ranvier. Associated with the novel niches filled by Nav1 channels in metazoans is the convergent evolution of completely differing sets of accessory Navβ subunits in different animal phyla or sub-phyla. Navβ subunits contribute to trafficking and stabilization of Nav1 channels to specialized nerve membrane locales. Navβ subunit isoforms serve as cell adhesion molecules tethering to elements to the extracellular matrix, and contribute to developmental functions such as nerve outgrowth and axon migration.